Complex evolution and the Triassic Tethyan‐type sedimentation in the Qinling Orogen. (20th October 2017) - Li, Yongjun; Duan, Fenghao; Zhang, Yuling; Zhi, Qian; Xu, Qian; Li, Shuling; Niu, Haiping
Abstract : The evolution of the Tethys Ocean is a significant geological event in global evolution history. However, although the hinterland of China has Tethyan sedimentary formations, the original extent of the Neo‐Tethyan Ocean remains vague and controversial. It has been confirmed that the Triassic strata in the Qinling Orogen is bounded by regional faults in the north and the south with an east–west‐trending distribution, as well as a scissor‐like linked to Paleo‐Tethyan flysch to the Bayakala area. The Qinling Orogen is characterized by great thickness and unique sedimentary formations, including deep‐water gravity flows, colluvial deposits, and olistostromes. Moreover, the Triassic strata have plastic rheology and buckling folds that are stronger than those of the adjacent pre‐Triassic strata in an aulacogen sedimentary setting. The original Yangtze‐type platform facies deposition in the Qinling rapidly switched into the Tethyan‐type aulacogen deposition after the Ladinian marine regression during the Middle Triassic. The Qinling Ocean was separated from the original and coeval Yangtze Ocean to the east and then connected with the Tethys Ocean to the west, and the orogeny started after the "emergency" closure of the basin during the late Middle Triassic to early Late Triassic. This unusual sedimentation and evolution highlight the uniqueness and complexity of the Qinling Tethyan‐type deposition. The Qinling Tethyan‐type Triassic formation is remarkably different from that of the Yangtze‐type platform facies Triassic formation in China recording the opening and closing of the Tethys Ocean within the mainland of China in the Triassic. The discovery and confirmation of the Triassic Tethyan‐type aulacogen sedimentation in the hinterland of China provide important evidence for further study of identification of the distribution and configuration of ocean and continent, and refinement and modification of the Tethyan Ocean of the global Triassic plate tectonic evolution.